Trends of English Language Teacher Education in Nepal - Pandit, Bhumi Raj (Kanya Journal, 2022)
This paper envisages the history and the trend of English language teacher education in Nepal. It reflects the outcome of the content analysis available on teacher education in the context of Nepal in printed materials and through online archives chosen purposively. For this, themes like teacher education in the past, teacher education in the ICT era and opportunities of continuous professional development in the context of Nepal were developed and authentic materials and documents relevant to the English language teacher education were analyzed, organized and reflection was written based on subjective interpretation. Analysis led to the conclusion that English language teacher education has a short history with remarkable achievements through continuous improvement. The provision of teacher education made by government and other organizations are found to have helped to maintain equalities and uniformities among teachers and professionals developing their career and imparting knowledge living in sophisticated area of the city center and the remote and rural areas of the multi-topographies of the country Nepal. However, the exposure the professionals have received in the comfortable zone has boosted the potentiality of them more in comparison to the ones who have been imparting knowledge, educating poor and marginalized people and earning livelihood in the remote areas.